Impact of steam inhalation, saline gargling, and povidone-iodine gargling on clinical outcome of COVID-19 patients in Bengaluru, Karnataka: A randomized control trial - Vani H Chalageri; Shobha Bhushan; S Saraswathi; T S Ranganath; V Devika Rani; Sumanth Mallikarjuna Majgi; Kariyappa Vijay; M S Hema; Shweta laxman Sanadi; P M Nasreen; K Md Shoyaib; Iswarya Partheeban; et al. (Wolters Kluwer Medknow Publications, 2022)
Context: In the absence of any specific treatment available for COVID-19, people started practicing traditional nonpharmacological preventive home remedies such as salt water gargling and steam inhalation. The available research evidence on some of these measures opines that steam inhalation, saline gargling, and povidone-iodine gargling does have virucidal properties and do provide symptomatic relief. Aims: The aim is to test this hypothesis, and the present trial was undertaken with an objective to assess the effect of steam inhalation, saline gargling, and povidone-iodine gargling among the COVID-19-positive patients with respect to early test negativity and clinical recovery. Methodology: Open-labeled, parallel, randomized controlled trial was conducted among asymptomatic or mild COVID-19-positive patients in Bangalore from September 2020 to February 2021. In each group of steam inhalation, saline gargling, povidone-iodine gargling, and control, twenty participants were allocated. Daily follow-up was done for 21 days to assess early test negativity and clinical recovery. Trial Registry Number: Clinical Trial Registry India/2020/09/027687. Results: Among 80 participants recruited, 65 (81.3%) were symptomatic. Early test negativity was seen in povidone-iodine gargling group of 6 days (KaplanMeier survival curve, BreslowGeneralized Wilcoxon test P = 0.7 as per the intention-to-treat and as per-protocol P = 0.8). Significant clinical recovery was seen in saline gargling group (4 days, P = 0.01). Conclusion: Povidone-iodine gargling was effective in providing early test negativity, whereas saline gargling was effective in early clinical recovery.